Lymphoepithelioma-like Carcinoma of the Urinary Bladder - Yun, Han Ki (The Korean Academy of Medical Sciences, 2010)
A 78-yr-old woman presented with gross hematuria for 2 weeks. On cystoscopy, a frond-like mass was observed at the bladder trigone. Transurethral resection of bladder tumor was performed for the mass. Histopathological findings showed that 90% of lesions were lymphoepithelioma-like carcinoma (LELCA) and a few lesions were non-invasive transitional cell carcinoma. On microscopy, syncytial growth pattern and indistinct cytoplasmic borders were observed with the severe infiltration of lymphoid cells. The case was followed-up for 8 months without recurrence. This is the first report of a LELCA case in Korea.